Renal Behcet's Disease: An Update - Akpolat, Tekin; Dilek, Melda; Aksu, Kenan; Keser, Goekhan; Toprak, Oemer; Cirit, Mustafa; Akpolat, Ilkser (W B Saunders Co-Elsevier Inc, 2008)
Objective: The aims of this study are (1) to report 33 patients with Behcet's disease (BD) having various renal manifestations, and (2) to update Current data using our patients and published papers about BD and renal manifestations. Methods: The PubMed database was searched using the terms BD or Behcet's syndrome. We found reports of 94 patients (including ours) with BD and specific renal diseases (amyloidosis, 39; glomerulonephritis [GN], 37; renal vascular disease, 19; interstitial nephritis, 1). Results: The presentation of renal disease was edema/nephrotic syndrome in 12 patients (36%). Renal disease was incidentally diagnosed by routine Urine analysis and measurement Of Serum creatinine level in 20 patients (61 %). Renal failure was present in 23 patients (70%) and 5 of them have had cyclosporine treatment. The frequency of renal disease among BD patients has been reported to vary from less than 1 to 29%. Conclusions: The clinical spectrum OF renal BD shows a wide variation. Amyloidosis (AA type), GN, and macroscopic/microscopic vascular disease are the main causes of renal BD. Patients with vascular involvement have a high risk of amyloidosis and amyloidosis is the most common cause of renal failure in BD. Several types of glomerular lesions are seen in BD. Current treatment options for renal BD are not evidence based. Radiological vascular intervention combined with immunosuppressive drugs can be useful in selected cases. Routine Urine analysis and measurement of serum creatinine level are needed Cor early diagnosis of renal BD. (C) 2008 Elsevier Inc. All rights reserved. Semin Arthritis Rheum 38:241-248
Keywords: Behcet's disease; amyloidosis; glomerulonephritis; renal vascular disease; interstitial nephritis; cyclosporine; uremia